Exploring teacher understanding of curriculum and assessment policy statement document implementation in South African schools - Sepadi, Medwin; Molapo, Karabo (Frontiers in Education, 2024)
Preparing subject teachers for understanding and implementation of curriculum and Assessment policy statement in schools has become a concern in nations as a way to strive for excellence. Yet, there is a little known about the understanding of curriculum policy than its effectiveness in the school. This study explored teacher understanding of Curriculum and Assessment Policy Statement (CAPS) document implementation. The study employed a qualitative approach, utilizing a case study research design. The interpretivism paradigm was applied to gain an in-depth understanding secondary of teachers’ perspectives on the implementation of the CAPS. The population of the research study consisted of 100 teachers in Capricorn District, and the sample of this study consisted of ten (10) teachers who were selected using a convenient sampling technique. Data was collected using individual, semi-structured interviews and focus group interviews, and was analyzed using thematic data analysis method. The study concluded that internal and external workshops could serve the purpose of implementing the CAPS document in the classroom. In addition, movable resources, for better implementation of the CAPS document in the classroom. Lastly, for researchers, these findings may help with further research on strategies to be implemented in schools to encourage constant use of the CAPS document. The unique contribution of this article to existing research on the classroom implementation of CAPS guidelines is to address the gap identified by ineffectiveness of the subject policy to the secondary teaching.